Menyiasati Rayuan Gombal Daya Tarik Duniawi (Sebuah Kajian Psiko-Filosofis dan Etis-Spiritual) - Fios, Frederikus (Humaniora, 2013)
The reality of the world is characterized by a cheesy seduction of attraction (temptation) that is very tempting every human. Temptations are full of charm, interesting, and contain a tremendous magnetism. Among the existing seductions, the appeal of power, sex, and wealth are three types of temptations that most often attract human attention. When a man drowned to follow the temptations, sooner or later he will experience individual and social destruction. Human tends to be selfish, hedonistic, and power abusive. These human’s actions are away from the principles of ethical-spiritual. A psycho-philosophical perspective is used as an entry point to understand the temptations referred, and with ethical-spiritual paradigm as a solution to resolve them. Humans are expected to be more mature in dealing with the temptations elegantly, and to wisely and ethically live life in dignity as spiritual beings.